Integrating greener, sustainable management tactics to minimise fall armyworm Spodoptera frugiperda (J. E. Smith) damage in maize - Soujanya, P. Lakshmi; Suby S.B.; S. Ramesh Babu; Jat, Shankarlal; Yathish, K.R.; Sharma, Romen; Subaharan, K.; Vinayan, Madhumal Thayil; Prasanna, Boddupalli M.; Sekhar, J.C.; Jat, H.S. (Springer, 2025)
The Fall armyworm (FAW), Spodoptera frugiperda (J. E. Smith), represents a polyphagous insect pest that incurs significant yield losses in maize on a global scale. This pest has extended its range from the neotropical regions of the Americas to Africa, Asia, and the Pacific. Maize cultivators primarily resort to chemical insecticides for the effective management of FAW. However, the indiscriminate application of these pesticides may lead to the development of resistance, toxicity to natural enemies, and environmental and human health risks, thereby necessitating the formulation of sustainable and environmentally friendly management strategies. This study examines the integration of various eco-friendly methods to alleviate FAW damage in maize crops. We assessed diverse sustainable pest management practises within different integrated pest management modules to combat FAW across four locations in the Telangana and Rajasthan states of India during the years 2023 and 2024. Key strategies incorporated the installation of pheromone traps equipped with FAW lures, the erection of ‘T’-shaped bird perches, the application of biopesticide formulations via spray, the release of Trichogramma chilonis cards, and the targeted use of newer-generation chemical compounds. Among these, Module 1 emerged as the most cost-effective and profitable. This module entails the installation of pheromone traps, ‘T’ shaped bird perches, a spray of azadirachtin at 1500 ppm at 5 ml per liter, a spray of Metarrhizium anisopliae formulation, followed by an additional need-based spray of chlorantraniliprole 18.5 SC; this approach significantly reduced the percentage of plant infestation and leaf damage ratings while exerting minimal impact on natural enemies compared to conventional farmers’ practice. Moreover, the cumulative effect of these practices yielded higher grain outputs of 50.55 and 48.0 quintals per hectare, resulting in improved cost-benefit ratios of 2.04 and 2.06 in comparison to farmers’ methods (46.18 and 43.00 quintals per hectare). Collectively, these integrated, sustainable approaches present viable solutions for managing FAW in maize, promoting both ecological equilibrium and agricultural productivity.